Tourism and staging heritage landscapes in the EL KALA National Park. Between preservation, eco valorization and setting in tourism - LATRECHE, Chafia; ROUAG, Djamila (Journal of Human Sciences, 2020)
The enhancement of landscapes for tourism purposes is a subject that exists little or no knowledge in Algeria. This study aims to highlight the values of the heritage landscapes of El Kala National Park, which is the object of preservation, eco-promotion and tourist promotion. Putting this heritage to tourism consists of understanding the concepts and values of the landscape considered as potential for attractiveness and tourism promotion, identifying all of the heritage potential, understanding the dynamics and vulnerabilities threatening the environment, to shed light on the current situation of tourism and to define the challenges and prospects that can contribute to the sustainable, economic and tourist development of the region.